2022
DOI: 10.1364/optcon.450150
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on high-reflective Fiber-Bragg-Gratings in multimode fibers

Abstract: Due to the large core diameter and high number of guided modes in fibers with large core diameters, increasing the reflectivity of Fiber-Bragg-Gratings (FBG) in these multimode (MM) fibers is technically challenging. To increase the homogeneity and reflectivity of FBG in MM fibers, we analyze the impact of laser inscription parameters onto the FBG dimensions. Limitations of the processable core volume due to the cylindrical fiber geometry are observed. A new inscription strategy is developed, utilizing the rot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Markus et al 6 demonstrated FBGs in multimode fibers to reduce costs in optical sensor systems, addressing parasitic mode effects using a mode transfer matrix formalism. Marius et al 7 utilized chirping combined with a new scanning technique to produce high-reflectivity FBGs in multimode fibers, achieving reflectivity of 61% and transmittance of 77%. Xu et al 8 focused on ultra-weak FBG arrays inscribed in single-mode fibers using a point-by-point technique for distributed high-temperature sensing, enduring temperatures up to 1000°C.…”
Section: Introductionmentioning
confidence: 99%
“…Markus et al 6 demonstrated FBGs in multimode fibers to reduce costs in optical sensor systems, addressing parasitic mode effects using a mode transfer matrix formalism. Marius et al 7 utilized chirping combined with a new scanning technique to produce high-reflectivity FBGs in multimode fibers, achieving reflectivity of 61% and transmittance of 77%. Xu et al 8 focused on ultra-weak FBG arrays inscribed in single-mode fibers using a point-by-point technique for distributed high-temperature sensing, enduring temperatures up to 1000°C.…”
Section: Introductionmentioning
confidence: 99%
“…Higher-order diffraction reflections also occur at submultiple wavelengths. However, when inscribed in multimode fibers, [6][7][8][9][10][11][12][13][14] FBGs show multiple reflection peaks around the fundamental Bragg peak. These multiple peaks originate from the coupling between different linearly polarized (LP) modes and can be utilized for discriminative sensing of distinct physical parameters.…”
mentioning
confidence: 99%
“…3). In spectra reflected from silica multimode FBGs, some small peaks sometimes appear around the fundamental Bragg reflection peak, [6][7][8][9][10][11][12][13][14] but no reflections are observed at other wavelengths. Thus, the generation of multiple FBG reflection peaks over an ultrawide wavelength range is a unique behavior of the POF-FBG, presumably caused by an eventual partial grating inscription in the POF core, resulting from the plane-by-plane femtosecond-laser inscription method used.…”
mentioning
confidence: 99%